2018
DOI: 10.1016/j.ijms.2017.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Separating and probing tautomers of protonated nucleobases using differential mobility spectrometry

Abstract: The protonated nucleobases (C + H) + , (T + H) + , (U + H) + , (A + H) + , and (G + H) + are investigated in a combined experimental and computational study using differential mobility spectrometry (DMS), mass spectrometry, and electronic structure calculations. DMS is used to isolate individual tautomeric forms for each protonated nucleobase prior to characterization with HDX or CID. The population distributions of each protonated nucleobase formed by electrospray ionization (ESI) are dominated by a single ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 46 publications
1
62
0
Order By: Relevance
“…Not only are protomers isomers-and therefore unable to be mass-resolved by mass spectrometry-changes in ESI conditions are observed to affect relative protomer populations. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] This can be an analytical problem when protomers dissociate to different product ions under activation, a phenomenon that can confound assignment by comparison to reference spectra. Differences in the photodissociation of protomers have been used to assign protomer populations, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] although it is difficult to predict how the electronic spectroscopy and photodissociation will be affected by differences in protonation site.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Not only are protomers isomers-and therefore unable to be mass-resolved by mass spectrometry-changes in ESI conditions are observed to affect relative protomer populations. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] This can be an analytical problem when protomers dissociate to different product ions under activation, a phenomenon that can confound assignment by comparison to reference spectra. Differences in the photodissociation of protomers have been used to assign protomer populations, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] although it is difficult to predict how the electronic spectroscopy and photodissociation will be affected by differences in protonation site.…”
Section: Introductionmentioning
confidence: 99%
“…FAIMS has proven to be a powerful tool for separating and analysing protomer populations at atmospheric pressure prior to detection by mass spectrometry. 1,4,6,8,46 Relative-energy calculations are typically coupled with FAIMS analysis to rationalise experimental results. However, it has been shown that theoretical results cannot reliably predict the relative protomer populations generated by ESI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We had detected multiple peaks for some purine derivatives, for example theobromine (see “nucleobases” in 3.2 ). Peak splitting of protonated nucleobases has been observed before and was attributed to the presence of multiple tautomeric forms of the same molecule [17]. However, the methylxanthines (MeX) investigated in this study produced single peaks and could therefore be regarded as present in only one tautomeric form.…”
Section: Resultsmentioning
confidence: 71%
“…The resolution between of amino-substituted adenine and its hydroxyl analog hypoxanthine, was determined to be R DMS =1.58. Based on recent literature [17], it is likely that tautomerism contributes to the DMS behavior of nucleobases and their derivatives. Untangling the individual contributions from these factors was outside the scope of this study, even though we observed multiple peaks in some cases (see below).…”
Section: Resultsmentioning
confidence: 99%